Nip7p Interacts with Nop8p, an Essential Nucleolar Protein Required for 60S Ribosome Biogenesis, and the Exosome Subunit Rrp43p - Zanchin, Nilson I. T. (American Society for Microbiology, 1999)
NIP7 encodes a conserved Saccharomyces cerevisiae nucleolar protein that is required for 60S subunit biogenesis (N. I. T. Zanchin, P. Roberts, A. DeSilva, F. Sherman, and D. S. Goldfarb, Mol. Cell. Biol. 17:5001–5015, 1997). Rrp43p and a second essential protein, Nop8p, were identified in a two-hybrid screen as Nip7p-interacting proteins. Biochemical evidence for an interaction was provided by the copurification on immunoglobulin G-Sepharose of Nip7p with protein A-tagged Rrp43p and Nop8p. Cells depleted of Nop8p contained reduced levels of free 60S ribosomes and polysomes and accumulated half-mer polysomes. Nop8p-depleted cells also accumulated 35S pre-rRNA and an aberrant 23S pre-rRNA. Nop8p-depleted cells failed to accumulate either 25S or 27S rRNA, although they did synthesize significant levels of 18S rRNA. These results indicate that 27S or 25S rRNA is degraded in Nop8p-depleted cells after the section containing 18S rRNA is removed. Nip7p-depleted cells exhibited the same defects as Nop8p-depleted cells, except that they accumulated 27S precursors. Rrp43p is a component of the exosome, a complex of 3′-to-5′ exonucleases whose subunits have been implicated in 5.8S rRNA processing and mRNA turnover. Whereas both green fluorescent protein (GFP)-Nop8p and GFP-Nip7p localized to nucleoli, GFP-Rrp43p localized throughout the nucleus and to a lesser extent in the cytoplasm. Distinct pools of Rrp43p may interact both with the exosome and with Nip7p, possibly both in the nucleus and in the cytoplasm, to catalyze analogous reactions in the multistep process of 60S ribosome biogenesis and mRNA turnover.